Stereoretentive Suzuki−Miyaura Coupling of Haloallenes Enables Fully Stereocontrolled Access to (−)-Peridinin - Woerly, Eric M; Cherney, Alan H; Davis, Erin K; Burke, Martin D (Journal of the American Chemical Society, 2010)
Stimulated by the substantial challenge of synthesizing the complex and sensitive stereogenic allene-containing core of (−)-peridinin, the first stereocontrolled coupling of haloallenes with boronic acids has been achieved. This new method and the principles that emerged during its development stand to enable the more efficient and flexible preparation of a wide range of natural products, pharmaceuticals, and intermediates that possess a stereogenic allene motif. This new reaction was harnessed to achieve the first completely stereocontrolled total synthesis of (−)-peridinin. This synthesis was accomplished using only one reaction iteratively to assemble four fully functionalized building blocks with complete stereoretention at each initial halide or boron-bearing carbon. This synthesis elevates the capacity of the iterative cross-coupling strategy to an unprecedented benchmark. Moreover, the efficient and highly modular nature of this synthesis promises to enable systematic dissection of the heretofore enigmatic structure/function relationships that underlie the protein-like antilipoperoxidant activities of this remarkable small molecule natural product.